"Operation sunshine": the rhetoric of a cold war technological spectacle - Griffin, Charles J. G. (My University, 2014)
This essay examines the role of the USS Nautilus (SSN 571), the world’s first atomic powered submarine, as an agency for advancing the Cold War objectives of the Eisenhower White House in the aftermath of the Soviet Union’s successful launches of Sputniks 1 and 2 and the early failures of the U.S. Vanguard program in late 1957 and early 1958. Specifically, it examines the campaign to exploit Nautilus for domestic propaganda purposes, which culminated in “Operation Sunshine,” the first submerged transit from the Pacific to the Atlantic oceans via the North Pole. The essay argues that architects of the technological spectacle faced the necessity of reconciling the material and symbolic aspects of the mission, and identifies three areas where this may have been necessary. In addition to illuminating the role of the Eisenhower White House in a significant, but largely forgotten episode in the Cold War, the essay illustrates the interplay of material and symbolic elements in Operation Sunshine and identifies some constraints that may be inherent in such technological spectacles.
Keywords: USS Nautilus; Cold War; Domestic propaganda; Operation Sunshine; Eisenhower White House